Using citizen science to obtain data on large, floating gelatinous spheres from NE Atlantic, attributed to egg mass of ommastrephid squid (Oegopsida, Cephalopoda, Mollusca). Issue 7 (9th August 2018) - Ringvold, Halldis; Taite, Morag
ABSTRACT: A total of 27 large, gelatinous spherical masses observed in coastal Norwegian waters from Nordland to Aust-Agder Counties in Norway, and off Lysekil in Sweden, Muljica Island in Croatia, Gulf of Naples in Italy, Reqqa Point in Malta, and Saint Mandrier in France, during the months of April to September 2001 to 2017, are reported. Individual spheres measured 0.3–2 m in diameter, averaging one metre ( n = 24, ±0.53 m), with all but four sighted in suspension in the water column between 0.5 and 52 m depth, in water temperatures ranging between 10–21°C. About half of all spheres contained a yellow-red streak through their gelatinous core. Tissue samples were not obtained. We attribute these gelatinous spheres to the egg masses of squid (Cephalopoda, Oegopsida), and most likely to the ommastrephid Todarodes sagittatus, given similarities with egg masses of T. pacificus .